Morphological differentiation between species of Myrmelachista Roger (Formicidae: Formicinae) in Atlantic Forest areas of the Alto Tiete (Sao Paulo) - Nakano, M. A.; Silva, R. R.; Miranda, V. F. O. [UNESP]; Feitosa, R. M.; Morini, M. S. C. (Univ Estadual Feira Santana, 2015)
Myrmelachista is an exclusively Neotropical ant genus. The ants from this genus nest and forage in live or dead trees, but data on its life cycle are relatively scarce. The taxonomy of this genus is considerably complex. The morphological characters of taxonomic importance are not well defined, and combining characteristics from the largest possible number of castes is thus essential. The goal of the present study was to present the results of multidimensional morphological analyses conducted based on morphometric measurements of workers and alates to help with the identification of Myrmelachista species. For that purpose, we gathered data from 277 specimens (workers, males and gynes) from eight species cohabiting Atlantic Forest areas. Eighteen morphometric variables were measured on workers and 20 on reproductive ants. Measurements related to eye size and mandible width were the variables more strongly associated with the two morphological clusters obtained based on the morphology of workers. However, the morphospace described by workers cannot be used to delimit the species of Myrmelachista. Mandible width, petiole height and eye size (eye length and ocelli width) were the most informative variables associated with the four clusters of morphology that clearly delimit males of M. arthuri, M. ruszkii sp.7, and in part, M. catharinae. Finally, petiole length and head length were the best descriptors of the six morphological clusters recognized for gynes. M. catharinae, M. sp.7, M. nodigera and M. gallicola were clearly delimited in the gyne morphological space. M. ruszkii showed high phenotypic variability, and this species was classified in two morphological clusters based on gyne specimens. Species identification employing multiple gyne morphological traits exhibited the best results. Our results show that morphospace analysis can be useful for delimitation of Myrmelachista species.
Keywords: twigs; arboreal ants; morphometric variables; multivariate analysis; taxonomy